Baitul Arqam: Perkaderan Mahasiswa Mencetak Generasi Agent of Change Masa Pandemi Covid-19 - Rokhmah, Islamiyatur; Hani, Umu (Jurnal Studi Islam dan Kemuhammadiyahan (JASIKA), 2023)
Regeneration (Perkaderan) is a necessity that is carried out by every organization including the 'Aisyiyah-Muhamamdiyah organization, this is done as an effort to produce future leaders to replace the leadership relay in an organization. Cadres in the era of Covid-19 will be said by some to be something that is impossible to do, but for progressive leaders nothing is impossible to do, the online model can still be carried out to nurture young cadres as generations of agents of change (change agents) in Covid-19 period 2019-2020. This research aims as a reflective study of the implementation of Baitul Arqom which has been carried out by 'Aisyiyah University (UNISA) Yogyakarta. The research method used a qualitative method by collecting data through observation, reviewing documentation and interviewing via Google forms with 767 students who took Baitul Arqom online at UNISA Yogyakarta. While the results of this study will be used as a reference for the Online cadre model for 'Aisyiyah and Muhammadiyah Universities.